Effect of Harvesting Time on Starch Degradation in Rumen of Whole-Plant Corn and Its Silage - Long Zhang; Shiqin Liu; Xuepeng Wang; He Wang; Songze Li; Yuguo Zhen; Xuefeng Zhang (Fermentation, 2025)
Whole-plant corn silage is a critical feedstuff in global ruminant production, and its nutrient composition is closely tied to harvest timing. As starch acts as the primary energy source in silage-based diets, investigating changes in starch degradation rate provides a theoretical basis for optimizing the efficient utilization of whole-plant corn and its silage in ruminant production. In this study, whole-plant corn (harvested from the milk stage to full ripening stage) and its corresponding silage were used as experimental materials. An in vitro simulated rumen fermentation system was employed to determine the contents of starch, prolamin, amylose, and amylopectin in the samples. The results showed that with delayed harvest time, starch content in both whole-plant corn and its silage increased significantly; prolamin and amylose contents first decreased, then increased; amylopectin content first rose significantly before decreasing; and both starch disappearance rate and speed exhibited a trend of first increasing, then decreasing. After silage fermentation, the silage had significant increases in starch, amylose, and amylopectin contents, and starch disappearance rate; prolamin content decreased; and starch disappearance speed increased extremely significantly. This study indicates that whole-plant corn harvest time and silage fermentation regulate the ruminal starch degradation pattern by altering starch structure, prolamin content, and the proportion of rapidly degradable starch.